2013
DOI: 10.18553/jmcp.2013.19.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Managing Specialty Medication Services Through a Specialty Pharmacy Program: The Case of Oral Renal Transplant Immunosuppressant Medications

Abstract: BACKGROUND: Immunosuppressive medication therapy after organ transplantation is essential for preventing transplant rejection and minimizing the need for re-transplantations. Nonadherence to immunosuppressant therapy has been identified as a major risk factor for acute complications and allograft rejection, as well as late graft rejection, and a return to dialysis after failed renal transplantation, leading to an increase in health care costs and potentially even death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 34 publications
1
32
1
Order By: Relevance
“…Furthermore, IMS claims data may not reliably describe prescribing practices in this population from the pre‐operative setting after listing for transplant through the immediate postoperative period, as medication changes may not be captured in a timely manner. As the patients included in this analysis may have been excluded from the registry study and as renal transplant recipients have shown better rates of compliance in specialty pharmacies, our study is pertinent to show that the disadvantages of PI‐based regimens may not confer across all populations …”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, IMS claims data may not reliably describe prescribing practices in this population from the pre‐operative setting after listing for transplant through the immediate postoperative period, as medication changes may not be captured in a timely manner. As the patients included in this analysis may have been excluded from the registry study and as renal transplant recipients have shown better rates of compliance in specialty pharmacies, our study is pertinent to show that the disadvantages of PI‐based regimens may not confer across all populations …”
Section: Discussioncontrasting
confidence: 99%
“…First, patients picking up their medication from a pharmacy might receive extra adherence‐enhancing interventions compared to those receiving them at the physician's office. Pharmacies are increasingly augmenting their services with adherence support, an intervention proven effective in kidney transplant patients 52, 53. Alternatively, receiving medication at a physician's office, which allows especially close follow‐up, might reflect the physician's perception of a higher nonadherence risk.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Patient Activation Measures23 and other self-report scales rely on direct assessment and results can be unpredictable due to human variability 24. As observed in their use with MTM, the quality of the data obtained is highly dependent upon the practitioner–patient relationship 25. The concordance of these types of measures with actual adherence behavior varies widely based on the skill of the practitioner 2628.…”
Section: Matching the Hammer To The Nail – Purposeful Measurementmentioning
confidence: 99%